The Dangers Of Narcotic Drags And The Way To Combat Them Through Legislations And The Judiciary (Al-Mansour Journal, 2022)
Human beings discovered long time ago some anesthetic plants and used their fibers and extracts in the medical prescriptions and religious rites, opium has been extracted from poppy from which Morphine and Heroine has been prepared in the 19 century. At the beginning of 20 century, there were no legal principles nor international censorship on the circulation of these anesthetics, the government depended on the national procedures according to the situation in each country and its population rate and technical potential, up to the time when many countries realized the risk that threatens their people because of agriculture and the production and circulation of anesthetics. The international community has approved in the first conference in Shanghai in 1959 the restriction on producing anesthetics to be produced only for scientific and medical needs, the misuse of anesthetics or the risk of their trade was widespread in the last two decades. Looking at what is the criminal risk and activating the legislation and the judiciary to combat them, we should discuss the risk of the anesthetics on the social interests instead of the criminal protection and show the reflections of the risk on the general principles of the law and the consequences of that on the law of combating drugs. In the first topics, we discussed the specific nature of anesthetics, in its material, scientific and financial characteristics and also in the corruption as a result of the misuse of anesthetics inside family, school and work. The second topic dealt with the reflection of the risk of anesthetics on general principles or the criminal law, we divided it into the reflection the legal principle and reflections whose risk is on the principle of criminal responsibility including the proposed responsibility.